Molecular Docking of the Pentapeptide Derived From Rice Bran Protein as Anticancer Agent Inhibiting Both Receptor and Non-Receptor Tyrosine Kinases - Gasymov, Oktay K; Keçel-Gündüz, Serda; Çelik, Sefa; AKYÜZ, SEVİM; Özel, Ayşen E.; Ağaeva, Gülşen; Süleymanova, Leman M.; Ağaeva, Ülker; Bakhishova, Matanat; Aliyev, JA (Taylor & Francis Inc., 2022)
The cationic pentapeptide Glu-Gln-Arg-Pro-Arg (EQRPR) belongs to the family of anti-cancer peptides with significant anti-cancer activity. However, the mechanism by which the peptide performs this activity is unknown. In this study, we explored the pharmaceutical profile of Glu-Gln-Arg-Pro-Arg pentapeptide and revealed its anticancer properties by in silico docking studies. Moreover, the effect of EQRPR behavior of the DPPC membrane was investigated by means of Langmuir monolayer technique and the results were discussed in terms of mutual interactions. To evaluate the binding mechanisms, the pentapeptide and its various D-amino acid substituted analogs were docked to both epidermal growth factor receptor (EGFR) tyrosine kinase and proto-oncogene tyrosine-protein kinase, Fyn. Simultaneous binding of the pentapeptides to both EGFR and Fyn proteins, which are receptor- and non-receptor-kinases, respectively, suggest that these peptides can be an effective agent for cancer treatment. Moreover, to show the potential of the investigated pentapeptides to overcome the generated mutation-related drug resistance to EGFR targeted therapies, molecular docking investigations of EQRPR and all its D-analogs were performed against the prospective targets: Wild type EGFR(WT) and mutant EGFR(T790M). Erlotinib and TAK-285 were used as reference molecules. The strong interaction of the peptide with EGFR(WT) (from -9.24 to -9.75 kcal/mol) and the secondary mutant EGFR(T790M) (from -9.28 to -9.64 kcal/mol) observed in most cancer recurrence cases indicates its good potential to overcome drug resistance in cancer therapy. In addition, the pharmacological properties of the investigated pentapeptides were revealed by in silico ADME (Absorption, Distribution, Metabolism, Excretion) and toxicity analysis. Communicated by Ramaswamy H. Sarma
Keywords: Anti-cancer Peptides; ADMET; EGFR and FYN Receptors; Langmuir-monolayer Technique; Molecular Docking